2018
DOI: 10.24310/riccafd.2018.v7i2.5093
|View full text |Cite
|
Sign up to set email alerts
|

Actividad física y calidad de vida en las personas mayores: estudio piloto PQS

Abstract: Agradecimientos: El estudio "Pasos que suman: programa saludable contra el sedentarismo en las personas mayores" ha sido financiado por las ayudas a los proyectos de Buenas Prácticas de Innovación Docente-USJ (2016). Los autores también desean dar las gracias a todos los voluntarios y a los centros participantes del municipio de Villanueva de Gállego, cuya colaboración y dedicación hicieron posible este estudio. Código UNESCO: 2312 Salud Pública Clasificación del Consejo de Europa: 17. Otras: Actividad Física … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One-third of diagnosed cancer cases could be prevented if exposures to various lifestyle-related risk factors were eliminated or reduced, such as smoking; consumption of harmful substances such as alcohol; an unhealthy, high-calorie diet with a high intake of saturated animal fats and sugars; and/or a sedentary lifestyle [ 1 , 4 , 5 , 7 ]. A large body of scientific evidence shows that physical activity has positive effects on the general population, improving health status, mood, body composition, quality of life [ 7 , 8 , 9 , 10 , 11 ], and preventing the onset of numerous diseases, including various types of cancer, such as breast cancer [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One-third of diagnosed cancer cases could be prevented if exposures to various lifestyle-related risk factors were eliminated or reduced, such as smoking; consumption of harmful substances such as alcohol; an unhealthy, high-calorie diet with a high intake of saturated animal fats and sugars; and/or a sedentary lifestyle [ 1 , 4 , 5 , 7 ]. A large body of scientific evidence shows that physical activity has positive effects on the general population, improving health status, mood, body composition, quality of life [ 7 , 8 , 9 , 10 , 11 ], and preventing the onset of numerous diseases, including various types of cancer, such as breast cancer [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies support a clear, positive relationship between physical activity and general health [21,25,[31][32][33][34][35], as well as physical [21,36], social [34,37] and psychological health [38], which is why physical activity should be a fundamental activity in the leisure time of adolescents [39][40][41]. Several studies [17,18,25,36,39] have shown the multiple benefits of regular and adequate physical activity on health behaviors and quality of life, as manifested by improved mood, greater resistance to stress, better physical condition and a better self-perception of health and quality of life [5,[42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of the present study was to determine the relationship between different levels of physical activity and self-perception of quality of life in a sample of adolescent students attending vocational education programs in physical activity and sports, because the practice of physical activity is considered a promoter of good health and quality of life [33,34,54].…”
Section: Introductionmentioning
confidence: 99%
“…One third of the diagnosed cancer cases could be prevented if exposure to various lifestyle-related risk factors were eliminated or reduced, such as the consumption of harmful substances such as smoking or alcohol, an unhealthy, high-calorie diet with a high intake of saturated animal fats and sugars, or a sedentary lifestyle [1,4,5,[7][8][9]. A large body of scientific evidence shows that physical activity has positive effects on the general population, improving health status, mood, body composition, quality of life [10][11][12][13][14], and preventing the onset of numerous diseases, including various types of cancer, such as breast cancer [12,15,16].…”
Section: Introductionmentioning
confidence: 99%